The siege of Macindaw - Flanagan, John (John Anthony) (New York, NY Puffin Books, 2010)
Will, who is now a full-fledged Ranger, must rescue his friend Alyss from a rogue knight and uncover vital information needed to ward off a Scotti invasion
"First published in the United States of America by Philomel Books ... 2009"--Title page verso
Includes excerpt from author's book 7 in the same series, "Erak's Ransom" in pages 1-16 at the end of the book
Includes excerpt from the author's book one, in the Brotherband Chronicles series, "The Outcasts."
Originally published: North Sydney, N.S.W. : Random House Australia, 2007
Accelerated Reader
1
Keywords: Araluen (Imaginary place) -- Juvenile fiction; Heroes and heroines -- Fiction; Heroes -- Juvenile fiction; Heroes; War stories; Coming of age -- Fiction; Courage in boys -- Fiction; Heroes -- Fiction; Rescues -- Fiction; War -- Fiction; Fantasy fiction; Fiction; Juvenile works; War fiction; War fiction